Diferentes consideraciones en torno al capital social de las sociedades cooperativas - Fernández Guadaño, Josefina (REVESCO. Revista de Estudios Cooperativos, 2006)
There has been on-going debate concerning the classification of the Social Capital of cooperative societies. This paper analyzes the different views on important areas of such classification. Particularly, it reviews the juridical approach in the European, national and autonomous environments; the national and international accounting methods; and the economic-financial approach. The goal is to overcome the existing discrepancies and to propose the partial refund of the partners’ contributions to Social Capital as a solution that attempts to guarantee the "Net Patrimony" nature of the non-mandatory portion of those social contributions, along with partially following the "open exit doors" cooperative principle.